Zdolności językowe i inteligencja w nauce języka obcego – teoria naukowa a praktyka dydaktyczna - Biedroń, Adriana (Neofilolog, 2017)
This paper is an attempt to shed light on cognitive factors in second language learning which are considered hardly modifiable, namely intelligence and foreign language aptitudes, including working memory. At first, each of the factors will be defined, the main research findings will briefly be outlined and some controversies and stereotypes surrounding the constructs will be presented. Next, the interface between research into these factors and teaching practice will be discussed. In particular, we will refer to ability training, aptitude-treatment-interaction and pedagogical suggestions concerning teaching mixed-ability classes.